Impact of a nurse-led intervention in understanding menstrual health management among adolescent girls attending specific schools in Navi Mumbai, India - Priya Naik; Smeeta Revankar; Vaishali Santosh Jadhav (MGM Journal of Medical Sciences)
Background: Premenstrual symptoms are prevalent among menstruating individuals, affecting around 75% of those who report some level of discomfort during their cycles. However, approximately 10% of women endure premenstrual syndrome (PMS), marked by symptoms that significantly disrupt daily functioning. PMS remains poorly comprehended and difficult to diagnose. The aim of this study was to assess the efficacy of an intervention and analyze the disparity in knowledge levels between the two groups. Materials and Methods: A genuine experimental design was employed using a pretest and post-test control group approach. A simple random sampling lottery method was used to select 40 adolescent girls for the study and control groups. These girls, aged 12–15 years, were chosen from specific schools in Navi Mumbai, adhering to predetermined inclusion criteria. A structured knowledge questionnaire was administered to both groups. At 1 week post-test, the study group received a nurse-led intervention through a planned teaching program. Data analysis included descriptive and inferential statistics. Results: In the control group, pretest knowledge scores averaged around 57.5%, suggesting a moderate level of knowledge. Conversely, the study group exhibited an average pretest knowledge score of 60%. Examining post-test knowledge scores, it is evident that in the control group, the majority (42.5%) demonstrated average knowledge, while in the study group, 67.5% exhibited excellent knowledge. Paired t test findings indicated a significant influence of the planned teaching program in the study group compared with the control group, with a P value of 0.001 at a significance level. Conclusion: Adolescent girls in the selected schools lacked knowledge about menstrual health management. Consequently, the nurse-led intervention on menstrual health management significantly improved knowledge among the control group of adolescent girls.